Alloperla clarki sp. nov. (Plecoptera: Chloroperlidae), a new species from the eastern Nearctic with discussion of a new species group - Grubbs, Scott A.; Baumann, Richard W. (Zootaxa, 2019)
Alloperla Banks, 1906 (Plecoptera: Chloroperlidae) is a speciose genus of spring- and summer-emergent stoneflies known from the Oriental, eastern Palearctic, and Nearctic realms. Over 50 species are currently recognized. Alloperla clarki sp. nov. is described herein from the adult male stage from a small geographic area in the Appalachian Mountains in Virginia and West Virginia, USA. Diagnostic characters are presented with scanning electron microscope (SEM) photomicrographs. Alloperla clarki sp. nov. most closely resembles A. biserrata Nelson & Kondratieff, 1980, A. nanina Banks, 1911, and A. stipitata Surdick, 2004. These four species share similar characteristics of the male epiproct and appear to comprise a species group. The Alloperla nanina Group is formally proposed. Comparative SEM images are also provided for A. biserrata, A. nanina, and A. stipitata to assist with differentiating between these four species.